2(5k+5)=4(k+4)

Simple and best practice solution for 2(5k+5)=4(k+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5k+5)=4(k+4) equation:



2(5k+5)=4(k+4)
We move all terms to the left:
2(5k+5)-(4(k+4))=0
We multiply parentheses
10k-(4(k+4))+10=0
We calculate terms in parentheses: -(4(k+4)), so:
4(k+4)
We multiply parentheses
4k+16
Back to the equation:
-(4k+16)
We get rid of parentheses
10k-4k-16+10=0
We add all the numbers together, and all the variables
6k-6=0
We move all terms containing k to the left, all other terms to the right
6k=6
k=6/6
k=1

See similar equations:

| 4+2p=10(3-5p-2 | | 2x-5=11+4x | | 3x+5=4x+-9 | | 51=6+7n | | 6(x−2)=−18 | | 8(-2x-4)=12=-52 | | 7y+4=-(4-7y)+8 | | -6x+1=14x-5 | | -(4z-)(11z+7))=7+(6z+4) | | 8-6(3x+2)=7 | | 7x^2+80x+100=0 | | 3x^2+4x-7=15 | | 9+2x-4/3=81 | | |4b-5|=19 | | -2k-3=4k-15 | | -12=3r+3r | | -(6x-1)=0 | | 11-1/2y=3+6y | | |3n-4|=-1 | | 2u^2-5u-18=0 | | -6x+1=14x5 | | 12=-3(2x+2)+7x | | |3n-4|=1 | | 90=12x+42 | | 3x/4-7/5=2x/10 | | 0.1x-0.6x-14=1 | | -3a+3+4a=10-21 | | x(4)=2x | | 6x-10=4x+22 | | 2+5.7t-4.9t^2=0 | | 2=​2/m−7 | | 1.5t^2-24t=0 |

Equations solver categories